Implementasi Administrasi Kependudukan Berbasis Digital di Kantor Kelurahan Kalisegoro - Khanaya Aulia Putri; Nina Oktarina (PUBLICNESS: Journal of Public Administration Studies, 2026)
The implementation of digital systems in population administration at the village level often reveals a gap between the ideal concept of e-government and practical reality on the ground. This study aims to examine and evaluate the implementation of digital-based population administration in Kalisegoro Village, Semarang City, with an emphasis on technological adaptation, data reliability, and service accessibility. Applying a qualitative case study approach through George C. Edwards III’s evaluation framework, data were collected via in-depth interviews and direct observation. The research findings indicate that digitalization successfully reduces bureaucratic procedures and increases transparency; however, it remains hindered by unstable central network infrastructure and challenges in migrating legacy data. The study concludes that the success of electronic government systems depends not only on technical factors but also on the synergy between digital efficiency and human-centric administrative considerations, such as the "pick-up and deliver" policy for elderly services. The uniqueness of this research lies in its strengthening of a management model at the grassroots bureaucratic level that combines technocratic efficiency with human values to bridge the digital divide. These findings provide a strategic contribution to developing a more inclusive and socially just public service ecosystem at the local level.